Desarrollo de Indicadores de Sostenibilidad Ambiental en la parroquia de Aláquez, cantón Latacunga, provincia de Cotopaxi. - Pilaguano Tipán, Jenifer Cristina (2022)
Environmental sustainability indicators help at the analysis, evaluation, making decision and land use planning, taking into account allocation and renewable use and non-renewable resources, as well as the need to develop activities in a given area. The present research work aims to facilitate implementation, control and adjustment of different activities that benefit to the community through development of sustainability indicators at social, environmental and economic areas from Aláquez parish. The used methodology was: qualitatively by bibliographic review on related topics to environmental sustainability and the study description area, the use of geographic information tools and quantitatively variables tabulation, which resulted on indicators development according needs of the parish allowing to provide solutions. Through gathered information was determined that 32% of inhabitants do not have access to drinking water, 41.18% are unemployed, 37% state that there is excessive use of pesticides by flower farms located in the area, causing ecosystem loss and affecting people health. It is also important that inhabitants of Aláquez parish and competent authorities become aware of the issue because there are serious problems, detrimental to human welfare and the environment.